МЕТАФОРАТА ВО ЈАЗИЧНАТА КОНЦЕПТУАЛИЗАЦИЈА НА ЕМОЦИИТЕ (СО ПОСЕБЕН ОСВРТ НА ФРАЗЕМИТЕ СО ЗНАЧЕЊЕ СТРАВ ВО МАКЕДОНСКИОТ И ВО РУСКИОТ ЈАЗИК) (Филолошки студии, 2019)
This article illustrates how important role metaphor plays in understanding a phenomenon as complex as the nature of emotion and how the human body influences the conceptualization of emotion. A lot of emotion metaphors are biologically rooted and based on physiologically conditioned responses to various stimuli. Well-known example of such biologically-based linguistic metaphor is fear is cold. The purpose of this article is to make a comparison of the metaphorical models applied on idioms denotiong fear in Macedonin and Russian language following the similar studies made for other Slavic languages.
Keywords: conceptualization of emotion, metaphor, fear, Macedonian language, Russian language